Characterisation of porcine dermis scaffolds decellularised using a novel non-enzymatic method for biomedical applications. (August 2015) - Greco, KV; Francis, L; Somasundaram, M; Greco, G; English, Nicholas R; Roether, Judith A; Boccaccini, Aldo R; Sibbons, P; Ansari, T
Off-the-shelf availability of tissue-engineered skin constructs, tailored by different combinations of reagents to produce a highly preserved biological matrix is often the only means to help patients suffering skin damage. This study assessed the effect of five different decellularisation methods on porcine dermal scaffolds with regard to matrix composition, biomechanical strength, and cytotoxicity using an in vitro biocompatibility assay. Results demonstrated that four out of the five tested decellularisation protocols were efficient in producing acellular scaffolds. Nevertheless, decellularisation method using osmotic shock without enzymatic digestion showed to be efficient not only in removing cellular material and debris from dermal scaffolds but was also beneficial in the preservation of extracellular matrix components (glycosaminoglycans and collagen). Histological assessment revealed that the dermal architecture of coarse collagen bundles was preserved. Examinations by scanning electron microscopy and transmission electron microscopy showed that the arrangement and ultrastructure of collagen fibrils in the scaffolds were retained following non-enzymatic method of decellularisation and also after collagen crosslinking using genipin. Moreover, this decellularised scaffold was not only shown to be biologically compatible when co-cultured with bone marrow-derived mesenchymal stem cells and fibroblasts, but also stimulated the cells to release trophic factors essential for tissue regeneration.